The Middle Pleistocene hominin mandible from Payre (Ardèche, France). Issue 144 (July 2020) - Verna, Christine; Détroit, Florent; Kupczik, Kornelius; Arnaud, Julie; Balzeau, Antoine; Grimaud-Hervé, Dominique; Bertrand, Simone; Riou, Bernard; Moncel, Marie-Hélène
Abstract: Although Neandertals are the best-known fossil hominins, the tempo and evolutionary processes in their lineage are strongly debated. This is in part due to the scarcity of the fossil record, in particular before the marine isotopic stage (MIS) 5. In 2010, a partial hominin mandible was discovered at the Middle Paleolithic site of Payre (France) in a layer that is dated to the end of MIS 8/beginning of MIS 7, a time period for which very few fossils are known in Europe. The Payre 15 mandible retains the complete symphyseal region and right lateral corpus with heavily worn P4, M1, and M2 in situ. Taphonomic modifications in the form of three notches suggest that this individual was chewed by a carnivore. We provide here the first detailed description of this specimen and a comparative analysis that includes morphological features, linear mandibular dimensions, an elliptic Fourier analysis of the symphysis, and a morphometric analysis of the M1 roots (based on segmented CT scan data). Our comparative sample encompasses European Middle and Upper Pleistocene specimens attributed to Homo heidelbergensis and Homo neanderthalensis, Upper Pleistocene Homo sapiens, and Holocene Homo sapiens . The Payre 15 mandible shows a combination of primitive and Neandertal-like features, with a receding symphyseal profile without any element of the mentum osseum, a posterior location of the mental foramen and lateral prominence. Its mandibular body is tall and thick anteriorly. Payre 15 has mesotaurodont M1 roots and a three-rooted M2. By its dimensions and combination of features, Payre 15 aligns better with Middle Pleistocene European hominins than with MIS 6–3 Neandertals. Noteworthy, it falls well within the range of variation of the Sima de los Huesos sample. Our results underscore that the total pattern of Neandertal-derived morphology was not achieved at the beginning of the MIS 7 and suggest a low level of mandibular diachronic changes for the period MIS 11–7.